1938
DOI: 10.1042/bj0322084
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of symbiotic nitrogen fixation

Abstract: BECAUSE of the practical importance of the problem in agriculture, research on the fixation of atmospheric nitrogen through association of the root nodule bacteria and leguminous plants has been primarily directed towards answering questions of immediate agronomic significance. As a result, advances concerned with the more fundamental aspects of this biological process have lagged behind practical applications. Part of the lag, however, may be ascribed to lack of suitable techniques for investigation of the bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1940
1940
1978
1978

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 2 publications
1
7
0
Order By: Relevance
“…We have already examined these claims in detail and rejected their specificity' (Wilson, 1939(Wilson, , 1940; Burris and Wilson, 1945). Briefly, our view is that most of the evidence could be applied equally well in support of the ammonia hypothesis.…”
Section: Identification Of the Initial Key Intermediatementioning
confidence: 96%
See 1 more Smart Citation
“…We have already examined these claims in detail and rejected their specificity' (Wilson, 1939(Wilson, , 1940; Burris and Wilson, 1945). Briefly, our view is that most of the evidence could be applied equally well in support of the ammonia hypothesis.…”
Section: Identification Of the Initial Key Intermediatementioning
confidence: 96%
“…Other inhibitors. Although most of the inhibitors commonly used in -enzyme research have been tested with both Azotobacter (Burk, 1934) and the symbiotic system (Wilson, 1939), none could be specifically associated with the fixation process. This means that if these inhibitors do affect the nitrogenfxing system, the inhibition cannot be detected, since they inhibit organisms .supplied with fixed nitrogen as well.…”
Section: Biological Nitrogen Fixationmentioning
confidence: 99%
“…Molecular hydrogen has been known for some years to be intimately concerned with nitrogen fixation. Wilson (125) showed that it was a com petitive inhibitor of fixation in red clover, and Hoch, Schneider & Burris (69) showed that it was evolved by soybean nodules in the absence of N2.…”
Section: Bergersenmentioning
confidence: 98%
“…They pointed out that the rapid oxidation of succinate might suggest that a four-carbon dicarboxylic acid cycle operates in rhizobia, but that this is doubtful because of the failure of the four-carbon dicarboxylic acids to show an increase in oxygen uptake on glucose above that expected from their direct oxidation. The utilization of succinate implies the presence of succinic dehydrogenase, thus accounting for the observed competitive inhibition of succinate oxidation in rhizobia by malonate and maleate (114). The participation of the tricarboxylic acid cycle, in addition to a pentose phosphate shunt, in the intermediary metabolism of the rhizobia might be suspected, but few specific facts are available.…”
Section: B Respiration and Cytochrome Systemmentioning
confidence: 99%
“…Because of the lack of control over the composition of the growth substrate and cell age in bacteroid studies, many of the respiratory differences found between nodular and cultured rhizobia may be of small significance. Apparently this has led several authors (95,114,115) to suggest that the respiratory responses of these cells are similar and that the same enzymes exist in both cases, although the extent of their activities differ. This opinion, although undoubtedly correct in many instances, should not negate the need for further research since relatively few enxymes have been directly compared.…”
Section: B Respiration and Cytochrome Systemmentioning
confidence: 99%